Ocena przygotowania przyszłych pedagogów szkolnych w perspektywie aktualnych badań = Assessment of the readiness of future school counselors in the perspective of current research - Kuźmik, Mateusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The main idea of this text was to review the readiness of school counselors in light of the current scientific sources. Students of various pedagogical specializations were the respondents in this research. Based on the current legal acts, the article describes the professional group of school counselors. It also contains information about the future, desired research directions in this field.
Keywords: przygotowanie; kształcenie; pedagodzy; szkoła; wymagania; readiness; education; school counselor; school; requirements